Distinct Successions of Common and Rare Bacteria in Soil Under Humic Acid Amendment – A Microcosm Study - Li, Pengfa; Liu, Jia; Jiang, Chunyu; Wu, Meng; Liu, Ming; Li, Zhongpei (Frontiers in Microbiology, 2019)
Humic acid (HA) is widely used for soil quality improvement, yet little is known how bacterial communities, especially common and rare bacteria, respond to HA amendment, which is crucial to understand biodiversity and function in agroecosystem. Therefore, a manipulated microcosm experiment with a gradient of HA amendment was conducted to unveil this. The results showed that common and rare taxa had similar patterns in species richness, while rare taxa exhibited a higher turnover, which caused their higher structural dissimilarity. Common species with wider niche breadths were more strongly influenced by deterministic filtering when compared to rare taxa, which occupied narrow niches and were primarily controlled by stochastic processes. Generally, species with wider niche breadths were always more strongly influenced by deterministic selection. The analysis of predicted functions revealed that rare taxa occupied more unique predicted functional traits than common taxa, suggesting that rare taxa played a key role in maintaining the functional diversity. In addition, there was a significant positive correlation between species richness and predicted functional diversity in rare taxa rather than common taxa. Our findings highlight the distinct structural and predicted functional successions of common and rare bacteria in soil under HA amendment.